MR arthrography of the hip: normal intra-articular structures and common disorders - El-Khoury, J. (2000)
This pictorial review illustrates the anatomical features of normal intra-articular components of the hip and their common disorders on MR arthrography. On T1-weighted MR arthrograms, the normal contrast-filled joint cavity shows a homogeneous high signal intensity. Normal acetabular labrum appears as a well-delineated triangle showing a low signal intensity, surrounded by contrast material in the perilabral recess. Intra-articular paramagnetic contrast outlines labral tears, loose bodies, communicating labral cysts and cartilage lesions (traumatic tears, focal defects, degenerative fissures and thinning), and improves their detection. Overall, MR arthrography enables accurate detection and staging of hip intra-articular structure abnormalities.